Fractal, fragmented, atomized: the singularity from a competitive perspective - Domingos Taufick, Roberto (Revista do IBRAC, 2023)
One can wonder how much could we have avoided if only we depicted today’s dilemma decades before. Having that in mind, this paper looks at long run developments in science in the so-called “Singularity” to shed light on how the future might look like. This work shows why it is likely that we will achieve not only one but many Singularities. It also claims that the atomization of the economy and more equal access to information will lead to fractal competition at the level of the algorithm, helping raise a society with more choices but also more fragmented.